Coiled Colonialities: Pianos and Place Signification in Shanghai’s Treaty Port History - Liao, Yvonne (Chopin Review, 2023)
Pianos find resonance in Shanghai’s treaty port history through their constant and changing inflections of coloniality, here understood as a deep-rooted historical condition replaying itself in strange, latent ways. Accordingly, this article explores the piano’s role as subject, enmeshed as it is within the treaty port as a peculiar plural setting, within the treaty port’s workings of music, power and place, and within the treaty port’s multiple entanglements with coloniality – in situ and over time. The piano, in a sense, lives vicariously through its allusions to colonialism’s hangover codes and structures. In turn, I conceptualise and investigate the piano (as) subject by cross-examining colonialities in and across French Shanghai of the 1930s and Chinese Nationalist Shanghai of the 1940s. Significantly, this discussion extends through temporal significations of place, revealing inner paradoxes of enclosure and experience, for one thing, and their regulatory manifestations across Shanghai’s treaty[1]port and post-treaty-port years, for another. Indeed, Shanghai’s French Concession in the 1930s, along with its incorporation back into the city’s Chinese Nationalist municipality from the mid to the late 1940s, are especially pertinent moments of inquiry, for these identified areas expose an underlying process of continuity-in[1]change, amid and despite the post-war resumption of sovereignty. Further such particularities help to eschew the rigidity of a foreign/indigenous dichotomy. Through observations of social order and ordering, as derived from the piano subject and its place signification, I explore the coiled workings of coloniality in Shanghai’s treaty port history, as well as interlocked meanings of power and perplexity, territory and ambience across licensed and taxable venues in the French Concession and the Chinese Nationalist municipality. Finally, from the treaty port setting, wider reflections follow on what I term ‘colonialities without recourse’, by which colonialities in the plural beget non-conclusive colonialities – in themselves awkward, yet telling, narratives of musical lives.